Skeletal responses to romosozumab after 12 months of denosumab. (3rd June 2021) - McClung, Michael R.; Bolognese, Michael A.; Brown, Jacques P.; Reginster, Jean‐Yves; Langdahl, Bente L.; Shi, Yifei; Timoshanko, Jen; Libanati, Cesar; Chines, Arkadi; Oates, Mary K.
ABSTRACT: Romosozumab, a monoclonal anti‐sclerostin antibody that has the dual effect of increasing bone formation and decreasing bone resorption, reduces fracture risk within 12 months. In a post hoc, exploratory analysis, we evaluated the effects of romosozumab after 12 months of denosumab in postmenopausal women with low bone mass who had not received previous osteoporosis therapy. This phase 2 trial (NCT00896532) enrolled postmenopausal women with a lumbar spine, total hip, or femoral neck T ‐score ≤ −2.0 and ≥ −3.5. Individuals were randomized to placebo or various romosozumab dosing regimens from baseline to month 24, were re‐randomized to 12 months of denosumab or placebo (months 24–36), and then all received romosozumab 210 mg monthly for 12 months (months 36–48). Results for the overall population have been previously published. Here, we present results for changes in bone mineral density (BMD) and levels of procollagen type I N‐terminal propeptide (P1NP) and β‐isomer of the C‐terminal telopeptide of type I collagen (β‐CTX) from a subset of women who were randomized to placebo for 24 months, were re‐randomized to receive denosumab ( n = 16) or placebo ( n = 12) for 12 months, and then received romosozumab for 12 months. In women who were randomized to placebo followed by denosumab, romosozumab treatment for 12 months maintained BMD gained during denosumab treatment at the total hip (mean change from end of denosumab treatment of 0.9%) and further increased BMD gains at the lumbar spine (mean change from end of denosumab treatment of 5.3%). Upon transition to romosozumab (months 36–48), P1NP and β‐CTX levels gradually returned to baseline from their reduced values during denosumab administration. Transitioning to romosozumab after 12 months of denosumab appears to improve lumbar spine BMD and maintain total hip BMD while possibly preventing the rapid increase in levels of bone turnover markers above baseline expected upon denosumab discontinuation. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.